2023
DOI: 10.1002/fsn3.3871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ficin‐hydrolyzed wheat gluten on bread quality and in vitro antioxidant activity before and after simulated gastrointestinal digestion

Mojan Seyedain‐Ardabili,
Mohammad‐Hossein Azizi

Abstract: This study aimed to investigate the effect of adding ficin‐hydrolyzed wheat gluten at different levels (0%, 1%, 2%, 4%) on bread quality, and in vitro antioxidant activity before and after simulated gastrointestinal digestion. Our findings revealed that the incorporation of the generated wheat gluten hydrolysates (WGH) up to 4 g per 100 g flour positively affected the technological and physical–chemical characterizations of breads, including dough rheological properties, color, specific volume, and moisture. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Their findings revealed that peptides with hydrophobicity and moderate molecular weight demonstrated the most potent ABTS radical scavenging activity. Consistent with these findings, Seyedain-Ardabili and Azizi [ 50 ] reported analogous results in their study on wheat gluten protein hydrolyzed with ficin. Their research revealed that the ABTS radical scavenging activity method exhibited higher antioxidant activity values compared to the DPPH radical scavenging activity method.…”
Section: Resultssupporting
confidence: 79%
“…Their findings revealed that peptides with hydrophobicity and moderate molecular weight demonstrated the most potent ABTS radical scavenging activity. Consistent with these findings, Seyedain-Ardabili and Azizi [ 50 ] reported analogous results in their study on wheat gluten protein hydrolyzed with ficin. Their research revealed that the ABTS radical scavenging activity method exhibited higher antioxidant activity values compared to the DPPH radical scavenging activity method.…”
Section: Resultssupporting
confidence: 79%